A Chemokine/Chemokine Receptor Signature Potentially Predicts Clinical Outcome in Colorectal Cancer Patients - Mitchell, Andrew (Cancer Biomark, 2019)
BACKGROUND: Differential expression of chemokines/chemokine receptors in colorectal cancer (CRC) may enable molecular characterization of patients’ tumors for predicting clinical outcome. OBJECTIVE: To evaluate the prognostic ability of these molecules in a CRC cohort and the CRC TCGA-dataset. METHODS: Chemokine (CXCL-12α, CXCL-12β, IL-17A, CXCL-8, GM-CSF) and chemokine receptor (CXCR-4, CXCR-7) transcripts were analyzed by RT-qPCR in 76 CRC specimens (normal: 27, tumor: 49; clinical cohort). RNA-Seq data was analyzed from the TCGA-dataset (n=375). Transcript levels were correlated with outcome; analyses: univariate, multivariable, Kaplan-Meier. RESULTS: In the clinical cohort, chemokine/chemokine receptor levels were elevated 3–10-fold in CRC specimens (P≤0.004) and were higher in patients who developed metastasis (P=0.03-<0.0001). CXCR-4, CXCR-7, CXCL-12α, CXCL-8, IL-17 and GM-CSF levels predicted metastasis (P≤0.0421) and/or overall survival (OS; P≤0.0373). The CXCR-4+CXCR-7+CXCL-12 marker (CXCR-4/7+CXCL-12(α/β) signature) stratified patients into risk for metastasis (P=0.0014; OR, 2.72) and OS (P=0.0442; OR, 2.7); sensitivity: 86.67%, specificity: 97.06%. In the TCGA-dataset, the CXCR-4/7+CXCL-12 signature predicted metastasis (P=0.011; OR, 2.72) and OS (P=0.0006; OR: 4.04). In both datasets, the signature was an independent predictor of clinical outcome. CONCLUSIONS: Results of 451 specimens from both cohorts reveal that the CXCR-4/7+CXCL-12 signature potentially predicts outcome in CRC patients and may allow earlier intervention.